ESTUDO DO PAPEL DA HISTIDINA, HISTAMINA E ANTAGONISTAS HISTAMINÉRGICOS NA PROGRESSÃO E DIFERENCIAÇÃO CELULAR EM UM MODELO DE MELANOMA MURINO - Berton, Juliana (2015)
Histidine is an important amino acid in the differentiation of some cell types, such as hepatocytes, for example. Histamine is synthesized from histidine is present in many cancer types, including melanoma. This cancer has as characteristics no differentiated cell and the production a high amount of histamine. The purpose of this work was to study the effects of a histidine supplementation on differentiation and tumor progression. In vitro cell viability were performed by neutral red and MTT assays with histidine at 0,01, 0,1, 0,3, 1,0, 3,0, 10 and 20 mM cimetidine at 0,01, 0,1, 0,3, 1,0, 3,0, 10 mM, 10 mM histidine association cimetidine + 0,01 mM and 10 mM cimetidine association + 0,01 mM histidine and evaluated after 24, 48 and 72 hours using B16F10 cells and morphological analysis additionally performed. Histamine at 0,01, 0,1, 1 and 10 mM, terfenadine at concentrations 1, 10, 100 nM and 1 uM and thioperamide at concentrations 1, 10, 100 nM and 1 uM were also assessed by using the MTT cell B16F10. ELISA was performed to quantify histamine with cell culture supernatant treated with histidine, histamine, terfenadine, cimetidine, and thioperamide. For in vivo assays were used C57BL6/J mice underwent implantation of tumor cells and subsequently treated with histidine solution at a dose of 21.4 mg/kg cimetidine 343.3 mg/kg and association between both and evaluated for 11 days as the tumor growth were used. Histological analysis, hematological and biochemical determinations were also performed. Data were analysed by ANOVA One-Way, and Tukey post-test. The results of the MTT viability test, showed cell viability decreased histidine at a concentration of 0,01 mM in 72 hours, cimetidine in concentrations 3 to 10 mM at 48 and 72 hours and cimetidine 10 mM /histidine 0,01 mM association in 48 and 72 hours, results also found in neutral red. Histamine decreased the cell viability of B16F10 cells at 20 mM concentration in 48 h and concentrations 1 and 10 mM at 72 hours, terfenadine decreased cell viability at all concentrations tested at 24 h and stayed up to 10 nM 72 hours and thioperamide decreased the cell viability at all concentrations tested 72 hours MTT assay. In the morphological analysis it was observed that at lower concentrations of histidine discrete cell rounding occurred and the appearance of "blebs" and the highest concentrations of vacuolated cytoplasm. Cimetidine treated cells showed characteristics of apoptosis. The association histidine 0,01 mM/cimetidine 10 mM caused cell death. The histamine ELISA test showed that the treatment with the histamine H1 antagonist may increase or decrease production of histamine and its receiving treatment led to thioperamide produce less or blocking of histamine H3 receptors allows a greater uptake of histamine. In experiments in vivo treatments with histidine and cimetidine inhibited tumor growth by the seventh day of treatment. Biochemical determinations of AST, ALT showed no toxicity after treatment. The histological findings, the group treated with histidine showed necrotic areas and the cimetidine group showed leukocyte infiltration and promoted stimulation of angiogenesis. Metastases were not found in any of the organs analyzed groups. It was concluded that histidine plays an important role in tumor progression and stimulating or inhibitory depending on the dosage/day of treatment.